Efeitos do exercício de intensidade fixa, autorregulada e da temperatura ambiente nas respostas metabólicas, termorregulatórias e perceptivas durante 30 km de ciclismo - Guilherme Passos Ramos (2012)
The present study aimed to evaluate the effects of self-paced and fixed intensity exercises and ambient temperature on metabolic, thermoregulatory and perceptive responses during 30km cycling. Participated in the study 8 cycling or mountain bike athletes (29 ± 1 years old). In the first visit to the laboratory, all volunteers were submitted to a graded exercise to evaluate maximal power output and oxygen consumption (VO2max), and were familiarized to the experimental exercise. The experimental situations consisted of 30km cycling in temperate (24ºC/68% RH) and hot (35ºC/68% RH) environment, with fixed (FIXO) and self-paced (AR) intensity in a total of four experimental situations. The exercises were performed on the athlete`s bike attached to an electromagnetic braking system, and separated by at least 7 days. The power output of the fixed intensity exercises was set using the mean power output held by the volunteers during AR exercises. This guaranteed that the time to complete the 30km, total workload and mean power output were similar between the exercises performed in the same environmental conditions. Data were analyzed using a three way ANOVA with repeated measures. RPE and thermal comfort were analyzed using Friedman test. There were no differences between AR and FIXO performed in the same ambient temperature on the mean values of the physiological variables studied. Only in hot environment the mean RPE, HR until kilometer 8, VO2 until kilometer 10, lactate concentration until kilometer 5 and rectal temperature from kilometers 4 to 22, were higher in AR compared to FIXO. Although mean HR and VO2 were not different between exercises in hot and temperate conditions, performance in the hot condition was impaired. Despite the lower power output observed in the hot condition, the increase in skin temperature and in rectal temperature were higher in this condition compared to temperate environment. The results of the present study indicate that there is no difference in thermoregulatory, metabolic and perceptive responsesbetween self-paced and fixed intensity exercises performed in temperate or hot conditions. Thereby it seems that fatigue mechanism is independent on the type of the exercise accomplished.